Dialektika Teologi dan Budaya dalam Gerakan Muhammadiyah: Kajian Kepustakaan Landasan Kultural Islam Berkemajuan - Nur Hakima Akhirani Nasution; Ahmad Lahmi; Dasrizal Dahlan (Jurnal Teologi Islam, 2026)
This article aims to analyze the cultural foundations of Muhammadiyah from the perspective of Progressive Islam (Islam Berkemajuan) through a library research approach. The study was conducted by examining scholarly literature published within the last ten years related to the cultural dynamics within the Muhammadiyah movement. The findings indicate that Muhammadiyah’s cultural foundation is an integral part of the purification and modernization processes that have been in place since the era of K.H. Ahmad Dahlan. The main findings reveal that the dialectic between normative theology and local culture has shaped a movement characterized by rationality, ethical values, and progressive orientation. Progressive Islam strengthens this dialectical pattern through three core principles: religious rationality, universal human ethics, and practical social engagement. This study fills a gap in previous research, which has not comprehensively examined the relationship between theology and culture within the framework of Progressive Islam. The implications of this article demonstrate that Muhammadiyah’s cultural foundation serves as an epistemological basis for developing an Islamic paradigm that is inclusive, moderate, and oriented toward civilizational advancement.